Economic evaluation of diagnostic tests for Thai patients with tuberculosis: A dynamic transmission model approach - Natthakan Chitpim; Naiyana Praditsitthikorn; Lisa J. White; Aronrag Meeyai; Jiraphun Jittikoon; Kornkanok Bunwong; Sitaporn Youngkong; Montarat Thavorncharoensap; Surakameth Mahasirimongkol; Wanvisa Udomsinprasert; Usa Chaikledkaew (PLoS ONE, 2025)
Conventional tuberculosis (TB) diagnosis is time-consuming, while newer molecular assays such as Xpert MTB/RIF and loop-mediated amplification test for TB (TB-LAMP) provide faster results but at a higher cost compared to sputum smear microscopy (SSM) with culture and drug susceptibility testing (DST) in Thailand. This study assessed the cost-utility of TB diagnostic algorithms as either initial or add-on tests from a societal perspective for TB diagnosis in the general Thai population. A dynamic transmission model was employed to evaluate five TB diagnostic algorithms over a 15-year period. Costs were calculated in 2023 Thai Baht, with results presented as incremental cost-effectiveness ratios (ICERs) compared to SSM with culture and DST. One-way and probability sensitivity analyses were conducted to assess parameter uncertainty. Compared to SSM with culture and DST, the ICER values (Baht per QALY gained) of TB-LAMP Add-On (3,563), Xpert MTB/RIF Add-On (3,670), and TB-LAMP Initial (6,429) indicated that these algorithms were cost-effective, while Xpert MTB/RIF Initial emerged as a cost-saving option. One-way sensitivity analysis results revealed that the utility of the first-line treatment exhibited the highest variability in ICERs, followed by the unit cost of Xpert MTB/RIF. The results supported the adoption of Xpert MTB/RIF as an initial test for the general Thai population. These findings provide evidence for policymakers to integrate molecular testing into Thailand’s Universal Coverage Scheme benefit package, aligning with national TB strategies to reduce TB incidence and mortality.